POSITION OF METABASITES OF CHEMERPIL STRUCTURE IN ROW OF THE BASITE COMPLEXES OF MIDDLE BOUG - HATSENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The study proved that Middle Boug metabasites are non-homogeneous by geochemical nature but they form a common trend from magnesia metabasites in direction of highferrous rocks. Hightitaniferous metabasites of Chemerpil structure are essentially differ from other metabasites by petrogenesis oxides and trace elements they contain. It is claimed that above mentioned rocks are belong to different magmatic process than other Chemerpil structures metabasites. Taking into consideration the similarity of Hightitaniferous metabasites of Chemerpil structure and basites anorthosite-rapakivi-granite association by chemical composition we can assume the following : Hightitaniferous metabasites of Chemerpil structure are the manifestations of dyke low-differentiated bodies of anorthositerapakivi-granite association in Middle Boug area.